Galectin-3 in Prostate Cancer Stem-Like Cells Is Immunosuppressive and Drives Early Metastasis - Caputo, Sara; Grioni, Matteo; Brambillasca, Chiara S.; Monno, Antonella; Brevi, Arianna; Freschi, Massimo; Piras, Ignazio S.; Elia, Angela R.; Pieri, Valentina; Baccega, Tania; Lombardo, Angelo; Galli, Rossella; et al. (Frontiers in Immunology, 2020)
Galectin-3 (Gal-3) is an extracellular matrix glycan-binding protein with several immunosuppressive and pro-tumor functions. The role of Galectin-3 in cancer stem-like cells (CSCs) is poorly investigated. Here, we show that prostate CSCs also colonizing prostate-draining lymph nodes of transgenic adenocarcinoma of the mouse prostate (TRAMP) mice overexpress Gal-3. Gal-3 contributes to prostate CSC-mediated immune suppression because either Gal-3 silencing in CSCs, or co-culture of CSCs and T cells in the presence of the Gal-3 inhibitor N-Acetyl-D-lactosamine rescued T cell proliferation. N-Acetyl-D-lactosamine also rescued the proliferation of T cells in prostate-draining lymph nodes of TRAMP mice affected by prostate intraepithelial neoplasia. Additionally, Gal-3 impacted prostate CSC tumorigenic and metastatic potential in vivo, as Gal-3 silencing in prostate CSCs reduced both primary tumor growth and secondary invasion. Gal-3 was also found expressed in more differentiated prostate cancer cells, but with different intracellular distribution as compared to CSCs, which suggests different functions of Gal-3 in the two cell populations. In fact, the prevalent nuclear and cytoplasmic distribution of Gal-3 in prostate CSCs made them less susceptible to apoptosis, when compared to more differentiated prostate cancer cells, in which Gal-3 was predominantly intra-cytoplasmic. Finally, we found Gal-3 expressed in human and mouse prostate intraepithelial neoplasia lesions and in metastatic lymph nodes. All together, these findings identify Gal-3 as a key molecule and a potential therapeutic target already in the early phases of prostate cancer progression and metastasis.